Genetic characterization of superior durian (Durio zibethinus L.) accessions in Batang District, Central Java, Indonesia based on ISSR markers - MUHAMMAD ISBAT AMRULLAH; ENNI SUWARSI RAHAYU; ELING PUWANTOYO; RIA IKA MAHARANI; SOLICHIN SOLICHIN; SRIYADI SRIYADI; TRI YANUAR HADIPRASETYA; AMIN RETNONINGSIH (Society for Indonesian Biodiversity, 2023)
Abstract. Amrullah MI, Rahayu ES, Puwantoyo E, Maharani RI, Solichin, Sriyadi, Hadiprasetya TY, Retnoningsih A. 2023. Genetic characterization of superior durian (Durio zibethinus L.) accessions in Batang District, Central Java, Indonesia based on ISSR markers. Biodiversitas 24: 4811-4819. Durian (Durio zibethinus L.) has the highest level of genetic diversity in the genus of Durio. The genetic diversity of D. zibethinus in Batang District, Central Java, Indonesia needs to be explored to obtain data on superior durian accessions that are adaptive in the area. This study aimed to analyze the genetic diversity of 40 superior durian accessions from 13 locations in Batang District using 10 Inter Simple Sequence Repeat (ISSR) primers. Genomic DNA was isolated from leaves using a modified CTAB method. PCR products were electrophoresed on 2% agarose and yielded 161 ISSR alleles with a percentage of 100% polymorphic alleles. The level of genetic diversity based on Nei's gene diversity and Shannon's Information index are 0.277 and 0.434, respectively. The durian accessions studied have a similarity coefficient of 0.22-0.86 and are divided into two main clusters. Siwatu 1 and Siwatu 2 accessions have the highest genetic similarity coefficient (0.86), while Butternuts and Watu Tembogo 1 accessions show the lowest genetic similarity coefficient (0.05). Specific alleles were found in 11 durian accessions. The molecular characterization results show the high genetic diversity of superior durian accessions in Batang District and add to the list of local superior durian accessions in Indonesia.